Comparison of discover cervical disc arthroplasty and anterior cervical discectomy and fusion for the treatment of cervical degenerative disc diseases: A meta-analysis of prospective, randomized controlled trials - Wang, Ziqi; Luo, Gan; Yu, Hongwei; Zhao, Hui; Li, Tianhao; Yang, Houzhi; Sun, Tianwei (Frontiers in Surgery, 2023)
Abstract Objective This study aims to evaluate the clinical efficacy and safety between Discover cervical disc arthroplasty (DCDA) and anterior cervical discectomy and fusion (ACDF) in Cervical degenerative disc diseases. Methods Two researchers independently conducted a search of PubMed, EMBASE, and Cochrane Central Register of Controlled Trails (CENTRAL) for randomized controlled trials (RCTs) following the Cochrane methodology guidelines. A fixed-effects or random-effects model was applied based on different heterogeneity. Review Manager (Version 5.4.1) software was used to perform data analysis. Results A total of 8 RCT studies were included in this meta-analysis. The results indicate that the DCDA group had a higher incidence of reoperation（P=0.03） and a lower incidence of ASD（P=0.04）than the CDA group. There was no significant difference between two groups regarding NDI score (P = 0.36), VAS ARM score (P = 0.73), VAS NECK score(P = 0.63) ，EQ-5D score（P = 0.61） and dysphagia incidence（0.18）. Conclusion DCDA and ACDF have similar results in terms of NDI scores, VAS scores， EQ-5D scores, and dysphagia. In addition, DCDA can reduce the risk of ASD but increases the risk of reoperation.